(untitled) - Mackay, Charles (New York, 1996)
Extraordinary Popular Delusions and Confusión de Confusiones take us from Tulipmania in 1634-when tulips actually traded at a higher price than gold-to the South Sea "bubble" of 1720, and beyond. Securities analyst and author Martin Fridson guides you on a quirky, entertaining, and intriguing journey back through time. Chosen by the Financial Times as Two of the Ten Best Books Ever Written on Investment Critical Praise . . . "This is the most important book ever written about crowd psychology and, by extension, about financial markets. A serious student of the markets and even anyone interested in the extremes of human behavior should read this book!" -Ron Insana, CNBC "In combining 'Extraordinary' with 'Confusion,' the result is not extraordinary confusion. Instead, with clarity, the book sears into modern investor minds the dangers of following the crowd.
Keywords: Common fallacies,Swindlers and swindling,Social psychology,Investments,Stock exchanges; Psychological aspects,Psychological aspects